Performance Evaluation of Semiplastic Recycled Cold Asphalt Using Noncement Binders - Byung Jae Lee; Jin Wook Bang; Jeong Su Kim; Young Il Jang (Advances in Materials Science and Engineering)
The optimal mixing conditions for semiplastic recycled cold asphalt, which recycled waste asphalt and used noncement binders (NCB), were assessed through verification of the performance. The NCB of 6% desulfurization gypsum mixing was found to have the most outstanding properties. For the Marshall stability, 4% (NCB) filler mixing brought about a 1.92-time strength increase effect compared to OPC (2%) and was improved when using modified asphalt and SBR. The flow test results showed that although an increase dosage of filler and SBR decreased the flow value of the semiplastic recycled cold asphalt, an increase dosage of asphalt emulsion improved the flow value. The indirect tensile strength and liquid immersion residual stability for the condition with greatest Marshall stability were most outstanding with 0.95 MPa and 83.6%, respectively. Evaluation of the recycled cold asphalt abrasion durability revealed that for the case of mixing more than 4% NCB the mass loss rate was lower than 20%. The abrasion durability was found to improve when using modified emulsified asphalt and SBR substitution. From the test results, it was found that the optimal mixing proportion of semiplastic recycled cold asphalt satisfied mechanical properties and durability is NCB with 4%, emulsified asphalt with 3%, and SBR substitution with 20%.